Waardinburg syndrome - inherited deafness with pigmentary involvement - M.F. Macrae (AOSIS, 1979)
The Waardenburg syndrome was first clearly defined in 1951. The major clinical importance lies in the fact that about 20% of affected individuals are deaf. Furthermore, because the condition is inherited autosomal dominantly, there is a risk of the disorder being handed down from generation to generation. The syndrome consists of six major features which may appear in any combination and to any degree in the affected individual.